1996
DOI: 10.1007/bf03349875
|View full text |Cite
|
Sign up to set email alerts
|

Cyproheptadine treatment in Cushing’s disease

Abstract: Cyproheptadine, a nonselective 5-hydroxytryptamine receptor blocking agent, reduces ACTH and beta-endorphin secretion from the ACTH-producing tumors. A 35-year-old female suffering from Cushing's disease due to microadenoma of the pituitary gland has been followed since the age of 15. Subtotal adrenalectomy followed by total adrenalectomy, pituitary irradiation, and transsphenoidal hypophysectomy, combined with second radiotherapy of the pituitary, were unsuccessful in achieving remission of the disease. Remis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 32 publications
0
7
0
2
Order By: Relevance
“…However, clinical studies showed disappointing results (Nieman 2002, Biller et al 2008. Control of CD activity with cyproheptadine has been described in case reports (Tanakol et al 1996) at doses varying from 12 to 24 mg/day. Main side effects are somnolence, hyperphagia, and weight gain.…”
Section: Cyproheptadinementioning
confidence: 99%
“…However, clinical studies showed disappointing results (Nieman 2002, Biller et al 2008. Control of CD activity with cyproheptadine has been described in case reports (Tanakol et al 1996) at doses varying from 12 to 24 mg/day. Main side effects are somnolence, hyperphagia, and weight gain.…”
Section: Cyproheptadinementioning
confidence: 99%
“…Bromocriptine, cabergoline and the serotonin antagonist cyproheptadine have been used in attempts to inhibit ACTH secretion in CD. After the early report of the use of cyproheptadine by Krieger et al ., there have been few further reports of its successful use, and in our own study in NS, cyproheptadine alone or with bromocriptine was ineffective 78–81 …”
Section: Medical Managementmentioning
confidence: 99%
“…Existen experiencias iniciales del uso de antagonistas serotoninérgicos, como cipro heptadina en dosis de hasta 24 mg, diarios con respuestas parciales 71 . Sin embargo, el empleo de este fármaco no se ha demostrado eficaz en la EC.…”
Section: Otros Tratamientosunclassified